(untitled) (Revista de Investigaciones Universidad del Quindío, 2009)
This work categorizes the pedagogical discourse in the classrooms of the University of Quindio by using procedures of ethnographic research. From this categorization it was concluded, among several aspects, that the discourse and the pedagogic practice at this university let people professionalize, and that the relationship between both aspects is asymmetric.